Legal nature of insurance contracts in civil aviation - Троцюк, Ніна Валеріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article focuses on research of particularities of subjective structure of an insurance contract in civil aviation, types of insurance contracts in civil aviation, as well as content of insurance contract and order of its conclusion and termination.